Pengembangan Jarimatika melalui Model Pendekatan Deep Learning pada Siswa SDN Tegal Pasir - Nailatul Faiseh; Kunsa Nabila Yetalia; Lela Nur Safrida; Fairiz Putri Salsabila; Noverita Oktavia Feninda; Salwa Oktaviyoni Ramadhani; Siti Kharimatul Hasana; Setia Hellena Putri; Mailulah Ely Fauziyah; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This social project aims to enhance elementary school students' interest and mathematical abilities through a deep learning-based mathematics learning model integrated with quick calculation techniques (jarimatika). The program was conducted at SDN Tegal Pasir, Jambesari Darus Solah District, Bondowoso Regency, involving 68 students from grades 1 to 6. The deep learning method applied emphasizes student-centered learning, hands-on practice, critical and creative thinking, and interactive discussions between students and facilitators. The application of quick calculation techniques in mathematics learning increased students' enthusiasm and active participation in learning activities. Results showed a 40% improvement in students' learning interest and numeracy skills compared to initial conditions. The deep learning-based mathematics learning model combined with quick calculation techniques proved effective in improving elementary school students' understanding, calculation speed, and interest in learning mathematics.